2014
DOI: 10.1111/maec.12148
|View full text |Cite
|
Sign up to set email alerts
|

Diel activity and short‐distance movement pattern of the European spiny lobster, Palinurus elephas, acoustically tracked

Abstract: This paper presents the results of the application of an ultrasonic telemetry system to the investigation of short‐term movements in the European spiny lobster, Palinurus elephas, in a coastal area of NW Sicily (Central Mediterranean Sea). Ten lobsters were tagged with miniaturized transmitters and released over a favourable habitat and their movements then recorded by means of nine automated receivers with the objective of investigating post‐release displacement, home‐range extension, movement patterns, activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Outliers (°) are presented only for the acoustic signal graph. Asterisks (*) represent significant differences between control and test conditions (grey asterisk for significant differences within the 1-male trials; black for significant differences within 2-male trials) dency to increase sound emission rate and locomotor activities at night (Buscaino et al 2012, Giacalone et al 2015. In animals that are active nocturnally, such as Ovalipes spp.…”
Section: Discussionmentioning
confidence: 99%
“…Outliers (°) are presented only for the acoustic signal graph. Asterisks (*) represent significant differences between control and test conditions (grey asterisk for significant differences within the 1-male trials; black for significant differences within 2-male trials) dency to increase sound emission rate and locomotor activities at night (Buscaino et al 2012, Giacalone et al 2015. In animals that are active nocturnally, such as Ovalipes spp.…”
Section: Discussionmentioning
confidence: 99%
“…However, their bipartite life cycle coupled with larval behaviour and varying patterns of ocean circulation result in differing levels of connectivity across populations (Metaxas and Saunders 2009;Incze et al 2010). Direct measures of connectivity, such as tracking individual animals and physical tag-recapture studies, have successfully identified adult lobsters' movement and migration (Booth 1997;Giacalone et al 2015;Skerritt et al 2015). Adults of some species such as Jasus edwardsii have very limited movement, travelling less than one kilometre per annum (Gardner et al 2003;Barrett et al 2009).…”
Section: The Role Of Oceanic Features and Larval Behaviour On Dispersalmentioning
confidence: 99%
“…Information is reported for each species in each study. UD 95% was used as home range descriptor in all the studies except in Giacalone et al, 2015, where authors adopted MCP 100%. "Protection level" indicates if the study was carried out in fully protected area (FPA), partially protected (Buffer) and/or fished area (f.a.…”
Section: Resultsmentioning
confidence: 99%